BENTUK CAMPUR KODE BAHASA JAWA KE DALAM BAHASA INDONESIA PADA FILM BUDI PEKERTI KARYA WREGAS BHANUTEJA (ANALISIS SOSIOLINGUISTIK) - Risca Rohmatul Aziza; Sumiharti Sumiharti; Abdoel Gafar (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to analyze the form of Javanese code mixing into Indonesian in the film Budi Pekerti by Wregas Bhanuetja. The analysis of this study will answer the research questions and objectives of the study, namely, to describe the form of code mixing which includes, word form, phrase form and clause form. The method used in this study is descriptive qualitative with listening and note-taking techniques to obtain data. The research data source is the dialogue of the characters in the film, while the research data is in the form of speech containing Javanese code mixing into Indonesian. The results of the study show that the form of code mixing that appears in the film includes 65 dialogue excerpts in total with 46 word form excerpts, 13 phrase form excerpts and 6 clause form excerpts with the dominant frequency in the use of words. This finding indicates that code mixing is used as a communication strategy that reflects the socio-cultural background of the characters and at the same time strengthens the value of locality in the film. Thus, this study is expected to contribute to sociolinguistic studies, especially in understanding the practice of code mixing in audio-visual media.